ANALISIS PERAN GURU PAK DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VIII SMP NEGERI 1 PARANGINAN KABUPATEN HUMBANG HASUNDUTAN TAHUN PEMBELAJARAN 2017/1018 - Nahampun, Marine (IAKN Tarutung, 2018)
Abstract, This research aims to know of the percentage the role of teacher religion Christian education in improving the learning motivation of the students in grade VIII of SMP Negeri 1 Paranginan, Batu Utara regency in 2017/2018 academic years, with the hypothesis there is a the role of teacher religion Christian education in improving the learning motivation students in grade VIII of SMP Negeri 1 Paranginan 75% of the expected. Technique of analyzing data was statistic technique with type of research quantitative descriptive inferential research with 198 population of all students who are Christiant Protestant in grade VIII of SMP Negeri 1 Paranginan. 59 peoples were selected as the samples taken by random sampling technique. Research instrument in the form of a closed questionnaire prepared by the researchers, trial conducted to 30 people with the values validity of 0.364-0.666 ≥0.361, and reliability value r11=0.895. Analyzing data was indicated that test of hyphotesis: tcount≥ttable namely 15.81≥1.67. Thus, Ha accepted, the conclusion drawn from this study was the role of teacher religion Christian education in improving the learning motivation of the students in grade VIII of SMP Negeri 1 Paranginan, Batu Utara regency in 2017/2018 academic years was good, which means the expected 75% and obtained of 89.31%